2023
DOI: 10.3847/2041-8213/acc247
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Anomalous Electron Fluxes Induced by GRB221009A on CSES-01 Low-energy Charged Particle Detector

Abstract: High-energy, long gamma-ray bursts (GRBs) can be generated by the core collapse of massive stars at the end of their lives. When they happen in the close-by universe they can be exceptionally bright, as seen from the Earth in the case of the recent, giant, long-lasting GRB221009A. GRB221009A was produced by a collapsing star with a redshift of 0.152: this event was observed by many gamma-ray space experiments, which also detected an extraordinary long gamma-ray afterglow. The exceptionally large fluence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…The ARTEMIS spacecraft THB and THC carried particles measurements in the same mode: spin-resolution ESA and spin- +219 s for the shoulder, T0+225 s for the first peak, T0+256 s for the second peak, and T0+509 for third peak are indicated by the vertical dashed lines). The timing uncertainties of THEMIS spacecraft synchronization (∼0.1 s) and time resolution do not allow us to resolve the time shift between the GRB signal recorded on board THB and THE and the data recorded on board the LEO spacecraft presented in detail by Battiston et al (2023). Thus, we present a 1 s resolution version of the ESA and SST data to compare with the 1 s light curves of HEPP-L (Battiston et al 2023) and HEBS (Liu et al 2022).…”
Section: Time History Of Events and Macroscale Interactions Duringmentioning
confidence: 99%
See 3 more Smart Citations
“…The ARTEMIS spacecraft THB and THC carried particles measurements in the same mode: spin-resolution ESA and spin- +219 s for the shoulder, T0+225 s for the first peak, T0+256 s for the second peak, and T0+509 for third peak are indicated by the vertical dashed lines). The timing uncertainties of THEMIS spacecraft synchronization (∼0.1 s) and time resolution do not allow us to resolve the time shift between the GRB signal recorded on board THB and THE and the data recorded on board the LEO spacecraft presented in detail by Battiston et al (2023). Thus, we present a 1 s resolution version of the ESA and SST data to compare with the 1 s light curves of HEPP-L (Battiston et al 2023) and HEBS (Liu et al 2022).…”
Section: Time History Of Events and Macroscale Interactions Duringmentioning
confidence: 99%
“…These measurements from spacecraft particle detectors provide an alternative perspective that complements observations from the gamma-ray telescopes by providing high sampling rates capable of resolving the fine structure of bursts (Schwartz et al 2005;Terasawa et al 2005). GRB 221009A was detected in the electron flux measurements made by the HEPP-L charged particle detector on board the low Earth orbit (LEO) China Seismo-Electromagnetic Satellite (Battiston et al 2023). Battiston et al (2023) showed that the recorded anomalous signal of GRB 221009A in the electron fluxes originated from secondary electrons produced via photon absorption in the passive material of the detector.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observation of the prompt emission was initially reported by Fermi/GBM (T 0 = 13:17:00 UTC) (Veres et al 2022). In view of the extreme GRB flux, spanning from low-energy X-rays to very high gamma rays, detections were reported by numerous instruments, including detectors not built to detect GRBs such as GAIA, SOHO (ESA 2022), Solar Orbiter (Xiao et al 2022), CSES HPPL (Battiston et al 2023), and others. Most of the GRB-devoted telescopes and observatories were obviously triggered, many of them with severe problems from detector dead time, pileup, and telemetry saturation: Swift/BAT (Dichiara et al 2022); MAXI (Negoro et al 2022); Fermi/LAT (Bissaldi et al 2022); AGILE (Piano et al 2022;Ursi et al 2022); INTEGRAL (Gotz et al 2022); Konus-Wind (Frederiks et al 2022); Insight-HMXT (Tan et al 2022); STPSat-6/SIRI (Mitchell et al 2022); GECAM (Liu et al 2022); SRG/ART-XC (Lapshov et al 2022); and GRBAlpha (Ripa et al 2022)).…”
Section: Introductionmentioning
confidence: 99%